Reflections of First-Year Medical Students: Supports and Challenges in Studying - Idham Rahman, Muhammad; Qanitah Shahabuddin, Nurul; Ainun Syawal, Hasri (CV. Green Publisher Indonesia, 2025)
The first year of medical school is often perceived as stressful and demands adaptive learning strategies. This study aims to explore factors influencing learning outcomes among first-year students after completing the first module in the second semester. We analyzed reflective essays containing ten open-ended questions written by first-year students. A total of 60 first-year medical students were selected using total sampling. The main variables examined include students' satisfaction with learning outcomes, learning process, motivation, and stress levels, measured using a 5-point Likert scale embedded within the reflective task. The average scores were learning outcomes satisfaction (3.4), satisfaction with the learning process (4.0), motivation to continue studies (4.8), and stress level (4.1). Thematic analysis revealed key positive factors: ability to manage study time, family support, and senior assistance in learning are perceived. Conversely, excessive lecture content, less communicative lecturers, and procrastination are perceived as challenging factors. Overall, first-year students reported satisfactory learning experiences. Enhancing time management skills and providing structured support systems from family and seniors may improve student success. Faculty should consider adjusting academic workload and instructional strategies to support first-year medical students' achievement.